Intramural Ectopic Pregnancy Following Myomectomy. (19th July 2018) - Vagg, Deanne; Arsala, Lima; Kathurusinghe, Shamitha; Ang, W. Catarina
Intramural pregnancy is a rare form of ectopic pregnancy with early diagnosis essential for prevention of severe hemorrhage and uterine rupture. We report a rare case of an intramural ectopic pregnancy at 12 weeks gestation in a woman 1 year post open myomectomy. Both transvaginal ultrasound and magnetic resonance imaging were utilized as diagnostic aids in this case. The rare nature of this clinical scenario and lack of guidelines for management made clinical decision making difficult. Due to the size and location of the gestational sac, hysterectomy was deemed to be the safest modality, and a midline laparotomy, total abdominal hysterectomy, and bilateral salpingectomy was performed.